2018
DOI: 10.1021/acsami.8b06154
|View full text |Cite
|
Sign up to set email alerts
|

Strontium-Doped Bioactive Glass Nanoparticles in Osteogenic Commitment

Abstract: The present work has explored bioactive glass nanoparticles (BGNPs) and developed strontium-doped nanoparticles (BGNPsSr), envisioning orthopedic strategies compatible with vascularization. The nanoparticles were synthesized by the sol-gel method, achieving a diameter of 55 nm for BGNPs and 75 nm for BGNPsSr, and the inclusion of strontium caused no structural alteration. The nanoparticles exhibited high cytocompatibility for human umbilical vein endothelial cells (HUVECs) and SaOS-2. Additionally, the incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 59 publications
3
33
0
Order By: Relevance
“…Such effect has not been observed for other divalent cations. On the basis of this dual effect, several Sr 2+ -based medicines [12][13][14] and biomaterials [15,16] have been developed to treat osteoporosis, a bone disease that affects hundreds of millions of people worldwide [17,18]. However, Sr 2+ administration has a dose-dependent impact on bone formation [19] and high Sr 2+ doses have been associated with the development of skeletal diseases like osteomalacia in rats with renal failure [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Such effect has not been observed for other divalent cations. On the basis of this dual effect, several Sr 2+ -based medicines [12][13][14] and biomaterials [15,16] have been developed to treat osteoporosis, a bone disease that affects hundreds of millions of people worldwide [17,18]. However, Sr 2+ administration has a dose-dependent impact on bone formation [19] and high Sr 2+ doses have been associated with the development of skeletal diseases like osteomalacia in rats with renal failure [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The used ions were expected to have a positive influence on osteogenic differentiation, because of their important role in bone biology [19][20][21]. An increased osteogenic differentiation in the presence of ions like Ca, Sr and Mg has been shown in previous studies [22,23]. An increased extracellular calcium concentration can cause an increase of intracellular calcium through calcium channels and results in activation of important targets during osteogenic differentiation [24].…”
Section: Cell Response In the Presence Of Released Ionsmentioning
confidence: 94%
“…The results of Leite et al showed that the products generated by the dissolved nanoparticles promoted the expression of key genes and proteins associated with osteogenic lineages in hASCs. This effect has been significantly improved by the presence of strontium, which induces osteogenic differentiation even without the use of osteogenic inducers [ 308 ].…”
Section: Adipose Stem Cells and Regenerative Medicinementioning
confidence: 99%